(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The study is about a performance workshop that proposed acting in the present, in the face of the chaos caused by human actions on nature and the threat of extinction. The activity was carried out based on theoretical and practical research developed within the scope of the Professional Master’s Degree in Arts at the Federal University of Ceará (ProfArtes/ICA/UFC). The research adopted Practice as Research (PaR), exploring the experiences of students and the researcher himself in the classroom. The experience resulted in the creation of five performances — this study presented excerpts from the four performed by the students —, constructed collaboratively between the students and the researcher.